Behaviors of Oxide Film during Semisolid Brazing of SiCp/6063Al Composite Materials - Jing Xiao; Shun Li; Shuxin Bai; Jiuchun Yan; Degan Xiong (Advances in Materials Science and Engineering)
The semisolid brazing of SiCp/6063Al under an applied pressure using Zn-Al-Cu filler metal was investigated. The samples to be joined were heated from 380°C to 382°C, 386°C, 392°C, and 410°C under a constant pressure of 10 MPa, respectively. Effects of the temperature on microstructural evolution and deformation behavior of the filler metal, interfacial structure, and shear strength of the bonded joint were discussed, and the disruption behavior of the surface oxide film was studied. The results show that, after heating, the solid grains of the filler metal transform into a globular structure surrounded by liquid. The degree of sphericity and the liquid fraction tend to improve with increasing temperature. During the heating process, the deformation of the filler metal is first accomplished by plastic deformation of solid grains and then by intergrain sliding and liquid flow. The surface oxides are broken and stripped by a cocontribution of compressive and shear stress which is caused by depressing and sliding of solid grains along the composites. It is found that the heating of 380°C to 392°C under pressure is the optimum condition to disrupt the surface oxide films and obtain sound bonds. The mechanical test results show that the maximum shear strength of the bond joints is as high as 105 MPa, reaching 78% that of the parent materials.